In vitro antitumor activity, ADME-Tox and 3D-QSAR of synthesized and selected natural styryl lactones. (December 2019) - Vukic, Vladimir R.; Loncar, Davor M.; Vukic, Dajana V.; Jevric, Lidija R.; Benedekovic, Goran; Francuz, Jovana; Kojic, Vesna; Karadzic Banjac, Milica Z.; Popsavin, Velimir
Graphical abstract: Highlights: In vitro cytotoxic activity of new styryl lactones against PC-3 cells was analysed. ADME-Tox in silico predictions were performed. 3D-QSAR model of the compounds was established. Steric field feature on the cinnamic acid ester groups at C-7 is crucial for the activity. Abstract: Prostate cancer is a common cause of death in men and a novel treating methods should be developed. In order to find a new drug for prostate cancer, a series of novel conformationally constrained analogues of (+)-goniofufurone and 7- epi -(+)-goniofufurone, as well as the newly synthesized styryl lactones containing the cinnamic acid ester groups were evaluated for in vitro cytotoxicity against prostate cancer cell (PC-3). Furthermore, prediction of physicochemical characteristics and drugability as well as in silico ADME-Tox tests of investigated compounds were performed. The 3D-QSAR model was established using the comparative molecular field analysis method. According to obtained results, the tricyclic compounds 9 and 10 had the highest potency with IC50 < 20 μM. Evaluation of structural features through 3D-QSAR model identified steric field feature on the cinnamic acid ester groups at C-7 as a crucial for the cytotoxic activity. This research suggests that most of the analysed compounds have desirable properties for drug candidates and high potential in drug development, which recommend them for further research in treatment of prostate cancer. Furthermore, obtained 3D-QSAR model is able to successfully identify styryl lactones that have significant cytotoxic activity and provide information for screening and design of novel inhibitors against PC-3 cell line that could be used as drugs in treatment of the prostate cancer.